THE VALUE OF THE HERITAGE OF ABU ALI IBN SINA IN THE DEVELOPMENT OF YOUTH EDUCATION - Shahlo Khalilova (American Journals Publishing, 2023)
This article explores the significance of education in society and its role in shaping the younger generation amidst global moral crises and geopolitical challenges. Drawing from historical perspectives and pedagogy, the study advocates for a synergistic approach that combines national and universal values with modern educational trends. The article emphasizes the necessity of examining the scientific and spiritual heritage of past thinkers, particularly in the field of spiritual and moral education. It highlights the contributions of Ibn Sina, an influential philosopher of the Eastern Renaissance, who considered education as a holistic process encompassing mental, physical, aesthetic, and moral aspects. Ibn Sina's work, particularly his philosophical interpretation of morality, offers valuable insights for both theoretical researchers and practical educators. The article concludes by affirming the relevance of Ibn Sina's ethical ideas in contemporary spiritual and moral education, emphasizing their potential application in the upbringing of children and adolescents, as well as the professional training of future teachers.
Keywords: national values, modern educational trends, scientific and spiritual heritage, Eastern Renaissance, aesthetic and moral aspects, ethical ideas, education of teenagers.